Empowerment of Posyandu Cadres in Detecting and Preventing Stunting - Ecia Meilonna Koka; Etti Sudaryati; Heru Santono (Universitas Muhammadiyah Surakarta, 2022)
Medan City is one of the North Sumatra areas with stunting problems. Pulo Brayan Kota, West Medan District, is included in the ten villages with the highest stunting cases. Strengthening integrated service posts by improving cadres’ skills is essential to monitoring toddlers’ growth every month. This research was carried out at the same time as community service, which was carried out from June to August 2021. The activity began with a preliminary survey, training for 12 cadres of integrated service posts, and conducting food security training for 40 Family Cards. Cadre training is carried out by presenting and practicing measuring the height of toddlers with a pacemaker and recording the measurement results on the Towards Health Card. Food security activities are carried out by submitting and practicing catfish farming in buckets and growing vegetables vertically using bottles. The results obtained include improving the skills of Integrated Service Post cadres in measuring the height of toddlers and the community to be skilled in catfish farming and growing vegetables vertically, the results of which can be used to strengthen food security in households to reduce the growth rate of stunting.